Influence of body position on microcirculatory and autonomic responses during arterial occlusion in healthy adults - Robert Trybulski; Adrian Kużdzał; Gabriel Stanica Lupu; Wacław Kuczmik; Grzegorz Biolik; Magdalena Hagner Derengowska; Jakub Taradaj (PLoS ONE, 2025)
This study aimed to investigate how body position (supine, seated, and standing) influences post-occlusive reactive hyperemia (PORH) and autonomic nervous system activity, with implications for vascular health and the safety of blood flow-restricted (BFR) exercise. A prospective, within-subject design was implemented. Fifteen healthy participants (18–30 years) were evaluated across three experimental sessions. Each session involved one randomized body position. Arterial occlusion pressure (AOP), microcirculatory responses (resting flow [RF], biological zero [BZ], time to peak [TP], recovery time [TR]), and heart rate variability (HRV) parameters—average normal-to-normal interval (AVNN), standard deviation of normal-to-normal intervals (SDNN), low-frequency/high-frequency power ratio (LF/HF), and heart rate (HR)—were recorded using laser Doppler flowmetry, Doppler ultrasound, and Polar H10 chest sensors. Standing and sitting positions significantly increased AOP min and AOP 100% compared to supine (p = 0.003, r ≥ 0.62). Resting flow and BZ values were also significantly elevated in these upright positions (sitting and standing) (p = 0.003). Time to peak and recovery time were longest in the standing position (p = 0.003–0.009). HRV analyses revealed a significant decrease in AVNN from supine to sitting and standing (p = 0.003), while SDNN and LF/HF increased in upright positions (sitting and standing) (p < 0.013). Heart rate was significantly higher in standing vs. sitting (p = 0.006), but not between supine and sitting (p = 0.459). Body position markedly influences both microcirculatory dynamics and autonomic nervous system responses. Upright positions (sitting and standing) elevate AOP and alter HRV, suggesting increased vascular and sympathetic activity. These findings are critical for optimizing BFR protocols and assessing cardiovascular safety during postural changes.